Tunisian son of Said And the relationship of his entourage with the footnote Sabban - Al Asmari, Hassan bin Mohammed (Arab Journal for Sciences and Research Publishing, 2018)
This study dealt with one of the scientists who were interested in the science of grammar; Based on the analytical inductive approach, The purpose was to define Ibn Said through the statement of his name and descent, birth, growth and death, mentioned his elders and students, and then mentioned the most prominent qualities and news, and the position of the scholars and his correspondence to him and vice versa, And his writings where he has been in various sciences such as logic and theology, The aim of this study was to highlight his commentary on the explanation of Ashmouni, And the talk about it through the statement of its subject and the achievement of its name, and the sources I mentioned, and their editions and places of existence, And the relationship between them and the footnote Sabba, This study concluded that Ibn Said was intelligent, knowledgeable, There is no evidence for this from the one who leads to reading and teaching with his young age, This study also highlighted the works of Ibn Said, which shows the capacity of his culture with his young age, As it was written in several sciences such as logic, knowledge of the doctrines, and the sciences of grammar Arabic as " his entourage to explain the Ashmouni" , " and explain Shawad Ashmouni, And literary as " astronomy loaded with the essence of the universe" a book in which he collected his poetry and prose, And it was also concluded that the correct investigation of the name of Ibn Said's footnote is " the planetary phenomena of the processions of the processions" To say that Ibn Sa'id has benefited- or at least seen- from Sabban's footnote is not far from right.